The Impact of the Covid-19 Pandemic on Food Consumers' Awareness of Antimicrobial Resistance, OneHealth, and Animal Welfare Information on Food Labels - Regan, Áine; Sweeney, Sharon; McKernan, Claire; Benson, Tony; Hyland, John; Dean, Moira (Frontiers in Veterinary Science, 2021)
Covid-19 is a OneHealth crisis with far-reaching and unexpected impacts on many aspects of society. Previous OneHealth issues, such as antimicrobial resistance (AMR), have not received a similar level of attention or action from the public despite representing significant public health and economic threats to society. The current study aimed to explore whether the Covid-19 pandemic may act as a catalyst to increase public awareness related to OneHealth issues, in particular, AMR. This paper presents the findings from a survey carried out in September 2020 with a representative sample of food consumers on the island of Ireland ( n = 972). The survey revealed Covid-19 had increased awareness of AMR amongst 47% of respondents; increased awareness of connected animal and human health amongst 43% of respondents; and increased awareness of animal welfare information on food labels amongst 34% of respondents. A cluster analysis revealed how five distinct consumer segments had been impacted differently by Covid-19; and how these segments also differed across objective and subjective knowledge of antibiotic use practices in farming, AMR risk perception, and attributions of responsibility for action on AMR. Findings are discussed with respect to future efforts by the agri-food sector to communicate with the public about AMR and responsible antibiotic use in farming, and to motivate consumer changes, with particular emphasis on the implications for strategies that incorporate front-of-pack labelling.